2020
DOI: 10.1186/s12989-020-00367-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particulate matter on atherosclerosis: a link via high-density lipoprotein (HDL) functionality?

Abstract: Background: Exposure to air pollution has been associated with adverse effects on human health, and ultimately increased morbidity and mortality. This is predominantly due to hazardous effects on the cardiovascular system. Exposure to particulate matter (PM) is considered to be responsible for the most severe effects. Main body: Here we summarize current knowledge from existing epidemiological, clinical and animal studies on the influence of PM exposure on high-density lipoprotein (HDL) functionality and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 78 publications
0
15
0
1
Order By: Relevance
“…7 Another study conducted by Holme et al, a case study of the relationship between PM and HDL exposure, showed that exposure of fine particulate matter (PM2,5) and Ultrafine particulate matter (PM 0.1) caused a decrease in HDL levels through oxidative processes. 14 Research conducted by Fan et al, where the atherogenic index value of 112 samples compared to the total carbon, organic carbon, and elemental carbon components at PM2.5 showed that the three components of PM2.5 had a significant correlation the increase in atherogenic index value, total carbon. r=0.307, organic carbon r=0.287, elemental carbon r=0.252 (Fan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…7 Another study conducted by Holme et al, a case study of the relationship between PM and HDL exposure, showed that exposure of fine particulate matter (PM2,5) and Ultrafine particulate matter (PM 0.1) caused a decrease in HDL levels through oxidative processes. 14 Research conducted by Fan et al, where the atherogenic index value of 112 samples compared to the total carbon, organic carbon, and elemental carbon components at PM2.5 showed that the three components of PM2.5 had a significant correlation the increase in atherogenic index value, total carbon. r=0.307, organic carbon r=0.287, elemental carbon r=0.252 (Fan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…TMAO can upregulate scavenger receptors, such as cluster of differentiation 36 (CD36) and scavenger receptor class A type 1 (SR-A1), and promote the formation of foam cells, leading to development and progression of atherosclerosis ( 7 ). As mentioned previously, the TMAO is similar to that of oxidized low density lipoprotein (ox-LDL), which can promote the differentiation of monocytes into macrophages that scavenge ox-LDL and transform into foam cells ( 63 ). TMAO can also promote endoplasmic reticulum stress (ERS) by up-regulating SR-1 receptors, while downregulating ATP-binding cassette transporter A1 in macrophages ( 64 ).…”
Section: The Molecular Mechanism Of Tmao Aggravating Coronary Atherosclerosismentioning
confidence: 99%
“…PM 2.5 induces oxidative stress, increasing the apoptosis of foam cells via the mitochondrial apoptosis pathway [52]. PM 2.5 impairs HDL functions such as HDL-mediated cholesterol efflux, thus facilitating foam cell formation and accumulation [53]. Apoptotic cells are not quickly and efficiently engulfed and decomposed by phagocytes, resulting in secondary necrosis and the release of a large amount of pro-inflammatory cytokines and thus contributing to the development of the necrotic core [54].…”
Section: Pm 25 and Atherosclerosismentioning
confidence: 99%
“…Epidemiological evidence has shown that exposure to PM 2.5 reduces the anti-inflammatory and antioxidant capacity of high-density lipoprotein (HDL), and decreases the expression of antioxidant markers such as glutathione peroxidase (GSH) and superoxide dismutase (SOD) [67,129]. A review showed that particulate matter impairs HDL function via oxidative pathways [53]. Importantly, evidence has shown that exercise training enhances HDL functions, including cholesterol efflux capacity and antioxidant capacity, and protects against endothelial dysfunction induced by PM 2.5 [130] [111].…”
Section: Ambient Pm 25 Increases Vascular Endothelial Permeabilitymentioning
confidence: 99%